A prospective cohort study of the changing mental health needs of adolescents in custody. Issue 3 (9th March 2013) - Lennox, Charlotte; Bell, Vicky; O'Malley, Kate; Shaw, Jenny; Dolan, Mairead
Abstract : Objective: To investigate changes in mental health and other needs, as well as clinical and diagnostic 'caseness', in a sample of adolescents over a 6-month period following entry into a Young Offenders Institution in the UK. Design: Prospective cohort study. Setting: One Young Offenders Institution between November 2006 and August 2009. Participants: 219 male adolescents aged 15–18 years (M=16.56; SD=0.6) were assessed at baseline (median=4; range 0–26 days following reception into custody) on the Salford Needs Assessment Schedule for Adolescents (SNASA) and Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS). Participants were then reassessed at 3-month and 6-month postbaseline to document any change in mental health. Results: Of the initial baseline sample, 132 were still in the study at 3-month postbaseline and 63 were still available for assessment at 6 months. There were no differences between those who were not available for assessment at the three key stages in terms of demographic and criminological data. Over time there was a general improvement in mental health. While the proportion of participants with a mental health need (SNASA) did not change over time, symptom severity as measured by the SNASA did reduce significantly. When we assessed diagnostic 'caseness' using the K-SADS, three young people showed significant mental health deterioration. Conclusions: In line with previous studies, we found that symptoms in prison generally improved over time. Prison may provide an opportunity for young people previously leading chaotic lifestyles to settle into a stable routine and engage with services; however, it is unclear if these would be maintained either within the prison or on release into the community.